PENGARUH PENGALAMAN MEREK DAN CITRA MEREK MENGGUNAKAN LIPSTIK PURBASARI DI KOTA PALU - YANTI UTARI, DEBBI (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
Cosmetics is part of the lifestyle of women, so many students and career women are increasingly aware of the importance of cosmetics to meet the lifestyle that is clean, healthy, and comfortable and interesting to look at. Lipstick products are cosmetic products that are being phenomenal and become a trend that is followed by women. This study aims to analyze the influence of brand experience and brand image on consumer loyalty, brand experience on consumer loyalty, and brand image of consumer loyalty. This study is a type of causal research. The population in this study were those who bought Purbasari lipstick in Palu city twice. Sampling technique in this study using purposive sampling, with the number of samples of 100 people. Data collection using questionnaires. The analytical method used multiple linear regression analysis. The results showed that there are simultaneous influence of brand experience and brand image on consumer loyalty using Purbasari lipstick, there is influence of product quality to loyalty of consumer of lipstick Purbasari and there influence of customer value to consumer loyalty using Purbasari lipstick in Palu city.